Conceptual framework and empirical methodology for measuring multidimensional judicial ideology - Matej Avbelj; Janez Šušteršič (DANUBE: Law, Economics and Social Issues Review, 2019)
The article presents a conceptual framework and empirical methodology of an on-going research on the role of ideology in the decisions of the Slovenian Constitution Court. The literature review demonstrates that research on judicial ideology in the courts of European countries and international courts is still rare. This can be explained by conceptual, methodological and empirical challenges posed by this type of research. The article hence advances a conceptual framework which is, contra to the mainstream theoretical approach in the field, based on a multidimensional conception of ideology that is empirically operationalised along the economic, social and authoritarian dimensions with five possible ideological positions on each dimension. By applying the newly developed methodology to a sample of Court's decisions, it is demonstrated that this methodological approach is able to account for ideological differences between judges. This confirms that (judges') ideology is a complex multidimensional set of values and convictions that cannot be reduced to simply equating ideology with (possible) political affiliations.
Keywords: 330; Judicial Ideology; Multidimensional Methodology; Constitutional Court of the Republic of Slovenia; Objectivist Concept of Law